PENERAPAN MODEL PEMBELAJARAN INTERAKTIF AKADEMIS EMOSIONAL UNTUK PENINGKATAN PRESTASI BELAJAR (PTK pada mata pelajaran Bahasa Indonesia di kelas V SDN 86 Kota Bengkulu) - Yuliantini, Nani (PINUS: Jurnal Penelitian Inovasi Pembelajaran, 2017)
This research is aimed to improve learning achievement through the application of emotional academic interactive learning model in Indonesian language subjects in grade V elementary school. To achieve this goal used classroom action research methods in collaboration with the teacher model as a researcher. The study was conducted at SDN 86 Kota Bengkulu for three cycles. The result of the research showed that the application of interactive academic model of emotional learning can improve student's learning achievement in Indonesian Language subjects. An effective model is learning with an emphasis on loving care towards students with problems and classes in an integrated manner. The core of this model the role of teachers should be more affectionate, creative and improvise in helping student achievement.